RESPON PENGENDARA TERHADAP ADANYA TEMPAT PEMOTONGAN AYAM DI JALAN KORONG GADANG KECAMATAN KURANJI KOTA PADANG - Ilham Febrian; Surtani Surtani (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to (1) The effect of the waste (smell) of chicken slaughtering business on drivers and driving comfort in terms of concentration and focus on Korong Gadang road, Korong Gadang Village, Kuranji District, Padang City. This type of research used in this research is a descriptive type with a qualitative approach. The technique of collecting data in this research is by using observation, interviews and documentation. The informants involved in this study were 31 drivers who crossed the chicken slaughtering business on the Korong Gadang road, Kuranji District, Padang City. The results of this study show that (1) In the morning and during the day, motorists who cross are disturbed by the smell produced by the chicken slaughtering business on Korong Gadang Street, Kuranji District, Padang City, while in the afternoon the drivers passing through the business are not disturbed because they are no longer bothered. smell then the weather factor also affects the smell produced by the business in rainy weather the smell produced is more pungent. Furthermore, drivers who pass through the business are not disturbed in driving, they can still drive well without losing their concentration or driving focus. Whether it's crossing in the morning, afternoon or evening and in rainy or hot weather. Keywords: Response, Smell, and Crochet Comfort